Assessing New Developments in Collection Security - Knight, Barry (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
Recent developments offer the possibility of using a security marker that contains a unique code that cannot be forged, and which can be detected at very low concentrations even if attempts have been made to remove it. The way in which these systems work is explained, and some of their advantages and disadvantages for libraries are examined.